2015
DOI: 10.1002/jmv.24165
|View full text |Cite
|
Sign up to set email alerts
|

Japanese encephalitis associated acute encephalitis syndrome cases in West Bengal, India: A sero‐molecular evaluation in relation to clinico‐pathological spectrum

Abstract: Japanese encephalitis (JE) is a major public health problem in Asia and worldwide and it is responsible mainly for viral acute encephalitis syndrome (AES). The sole etiologic agent of JE is Japanese encephalitis virus (JEV). Although JE/AES cases have been regarded traditionally as a disease of children, a growing number of patients with JE/AES cases are also seen in the adult age group every year in the state of West Bengal, India in spite of vaccination. Therefore, a systematic study was performed to differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…According to our study, serological results were noted. The elevated level of CSF protein in pediatric and adult patients in the present study conformed to the published article (19). A previous study found that CSF protein levels were related to neurological symptoms.…”
Section: Discussionsupporting
confidence: 91%
“…According to our study, serological results were noted. The elevated level of CSF protein in pediatric and adult patients in the present study conformed to the published article (19). A previous study found that CSF protein levels were related to neurological symptoms.…”
Section: Discussionsupporting
confidence: 91%
“…JEV infection can induce endothelial cells and astrocytes to produce mediators that regulate JEV production while destroying the integrity of the blood-brain barrier ( Patabendige et al., 2018 ), increasing the CSF protein. A previous study discovered that CSF protein levels were linked to neurological symptoms, suggesting that abnormal intrathecal protein synthesis results in poor prognosis ( Sarkar et al., 2015 ). Furthermore, CSF sugar levels in patients with JE were either normal or slightly elevated.…”
Section: Discussionmentioning
confidence: 99%
“…21,22,66,67,[69][70][71] Other differences between children and adults have also been reported, but not consistently; these include a higher rate of neck stiffness, abnormal behavior, electroencephalogram abnormalities and a lower level of consciousness among children and higher mean or median cerebrospinal fluid white cell counts and protein levels among adults. 21,22,[65][66][67]69,71 Although results in studies of outcome following JE have again been variable, many studies suggest the case fatality rate might be higher among adults than children; however, among survivors, sequelae might be more frequent among children. 21,22,65,67,69,[72][73][74][75] This suggests that children with severe disease are more likely to survive but end up with severe neurologic and other sequelae.…”
Section: Disease Among Adultsmentioning
confidence: 99%